2021
DOI: 10.1016/s0140-6736(21)00246-4
|View full text |Cite|
|
Sign up to set email alerts
|

The SANAD II study of the effectiveness and cost-effectiveness of valproate versus levetiracetam for newly diagnosed generalised and unclassifiable epilepsy: an open-label, non-inferiority, multicentre, phase 4, randomised controlled trial

Abstract: Summary Background Valproate is a first-line treatment for patients with newly diagnosed idiopathic generalised or difficult to classify epilepsy, but not for women of child-bearing potential because of teratogenicity. Levetiracetam is increasingly prescribed for these patient populations despite scarcity of evidence of clinical effectiveness or cost-effectiveness. We aimed to compare the long-term clinical effectiveness and cost-effectiveness of levetiracetam compared with valproate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 35 publications
2
98
0
5
Order By: Relevance
“…For many years, carbamazepine was considered the first-line treatment for focal-onset seizures, and the standard treatment for focal epilepsy in clinical trials, whereas valproate, with its broad-spectrum efficacy, was, and still, recommended first-line treatment for generalized-onset and unclassified seizures. 8 , 9 , 41 43 These recommendations were based largely on the results of RCTs comparing carbamazepine and/or valproate with other older drugs. 44 – 51 A large meta-analysis by Marson and colleagues 52 emphasizes that carbamazepine and valproate are broadly similar in terms of clinical outcomes of efficacy, tolerability, and drug retention after randomization.…”
Section: Principles Of Asd Selectionmentioning
confidence: 99%
“…For many years, carbamazepine was considered the first-line treatment for focal-onset seizures, and the standard treatment for focal epilepsy in clinical trials, whereas valproate, with its broad-spectrum efficacy, was, and still, recommended first-line treatment for generalized-onset and unclassified seizures. 8 , 9 , 41 43 These recommendations were based largely on the results of RCTs comparing carbamazepine and/or valproate with other older drugs. 44 – 51 A large meta-analysis by Marson and colleagues 52 emphasizes that carbamazepine and valproate are broadly similar in terms of clinical outcomes of efficacy, tolerability, and drug retention after randomization.…”
Section: Principles Of Asd Selectionmentioning
confidence: 99%
“…Table 3 presents the efficacy of ASDs against common seizure types and epilepsy syndrome. The data supplemented in the table are based primarily on the results of RCTs comparing the newer versus older drugs, including the SANAD studies 34‐37 and others, 38‐62 and recently published meta‐analyses 63‐69 . Table 4 and the remainder sections of this article present guidance for ASD selection for the specific seizure type according to the 2017 ILAE classification of seizure types and epilepsy syndromes 14‐17 .…”
Section: Introductionmentioning
confidence: 99%
“…There has been a limited number of ASDs that can be used as first‐line agents for GTCS. Valproate remains the first‐line drug for many patients with generalized and unclassified epilepsies, 22,35,36,72 while phenobarbital (or primidone) is a primary drug in infants (for neonatal seizures) and an alternative in adults. However, valproate should not be prescribed for women of childbearing potential because of its dose‐dependent teratogenic profile; unless other ASDs cannot control the seizures, in which case the dose should be kept as low as possible 84 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 60% of people with epilepsy can achieve seizure control with antiseizure medication (ASM) monotherapy [ 2 ]. An increasing number of studies have demonstrated that valproate (VPA) and oxcarbazepine (OXC) continue to be commonly used ASMs for patients with epilepsy [ 3 , 4 ]. Meanwhile, concerns have been raised by patients and clinicians regarding the risk of sexual dysfunction, reduction of sperm quality, and sex hormone disorders in males with epilepsy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%